Micropropagation of an Exotic Ornamental Plant, Calathea crotalifera, for Production of High Quality Plantlets - Shahril Efzueni Rozali; Kamaludin A. Rashid; Rosna Mat Taha (The Scientific World Journal)
A successful protocol was established for micropropagation in two selected varieties of exotic ornamental plants, Calathea crotalifera. The effects of different sterilization techniques, explant type, and the combination and concentration of plant growth regulators on shoots induction were studied. The axillary shoot buds explants sprouted from rhizomes in soil free conditions showed high induction rate of shoots with lowest contamination percentage when treated with combination of 30% (v/v) NaOCl, 70% (v/v) ethanol, and 0.3% (w/v) HgCl2. In the present study, the highest number of multiple shoots was obtained in MS basal medium supplemented with 3.5 mg/L 6-Benzylaminopurine (BAP), 1.0 mg/L 1-Naphthaleneacetic acid (NAA), 3% sucrose, and 6 g/L plant agar for both varieties and was used as multiplication medium. Microshoots were highly induced when the young shoot bud explants were incised longitudinally prior subculture. Chlorophyll analysis was studied to test the effects of activated charcoal and L-glutamine on reduction of necrosis problem. The maximum roots induction was recorded on MS medium supplemented with 1.0 mg/L 1-Naphthaleneacetic acid (NAA) compared to indolebutyric acid (IBA). The complete regenerated plantlets were successfully acclimatized in the soilless medium under greenhouse condition. This is the first report of rapid mass propagation for C. crotalifera.